Corporate performance : a ratio-based approach to country and industry analyses - Koralun-Bereznicka, Julia (Contributions to Management Science, 2013)
This book presents the comparative evaluation of international and industrial factors affecting the financial condition of enterprises. In the theoretical part, the results of previous research on the occurrence of the country and industry effect in the financial health of companies are reviewed. The aim of the empirical study is to determine such factors - national or industrial ones - that have a greater impact on the corporate performance in the selected European Union countries. Corporate performance is measured and described with the use of a large set of fundamental ratios. Corporate performance is therefore treated as a more complex matter influenced by such aspects as profitability, liquidity, working capital and solvency. The book especially analyses the importance of non-public companies of all sizes, which is also rare as current research focuses mainly on public companies due to the data constraints.